Examining the Auroral Ionosphere in Three Dimensions Using Reconstructed 2D Maps of Auroral Data to Drive the 3D GEMINI Model. Issue 11 (15th November 2021) - Clayton, Robert; Burleigh, Meghan; Lynch, Kristina A.; Zettergren, Matt; Evans, Tucker; Grubbs, Guy; Hampton, Donald L.; Hysell, David; Kaeppler, Stephen; Lessard, Marc; Michell, Robert; Reimer, Ashton; et al.
Abstract: We use the Geospace Environment Model of Ion‐Neutral Interactions (GEMINI) to create three‐dimensional, time‐dependent simulations of auroral ionospheric parameters in the localized, several 100 km region surrounding auroral arcs observed during a winter 2017 sounding rocket campaign, resolving three‐dimensional features of fine‐scale (km) flow structures in the vicinity of an auroral arc. The three‐dimensional calculations of GEMINI allow (with sufficient driving data) auroral current closure to be investigated without idealizing assumptions of sheet‐like structures or height integrated ionospheres. Datamaps for two nearly sheet‐like arcs are reconstructed from replications of the Isinglass sounding rocket campaign data, and combined with camera‐based particle inversions into a set of driving inputs to run the 3D time‐dependent model. Comparisons of model results to radar density profiles and to in situ magnetometry observations are presented. Slices of volumetric current, flow, and conductance structures from model outputs are used to interpret closure currents in an auroral arc region, and are compared to original in situ measurements for verification. The predominant source of return current region field aligned current closure for these slow time variation events is seen to be from the conductance gradients, including the Hall. The importance of the ∇ Σ H versus ∇ Σ P terms in the determination of the current structure provides a more complicated picture than a previous GEMINI study, which relied predominantly on the divergence of the electric field to determine current structure. Sensitivity of data‐driven model results to details of replication and reconstruction processes are discussed, with improvements outlined for future work. Key Points: Three‐dimensional physics‐based Geospace Environment Model of Ion‐Neutral Interactions (GEMINI) ionospheric model driven with two‐dimensional reconstructions of auroral data for non‐idealized view of auroral current closure Conductance gradients are shown to be significant for current closure in these examples, including Hall conductance gradients in some cases Exploration of sensitivity of GEMINI output to fidelity of data reconstruction input drivers at radar and in situ resolutions